FAKTOR - FAKTOR YANG MEMPENGARUHI SUSTAINABLE DEVELOPMENT PADA PERUSAHAAN SEKTOR F&B YANG TERDAFTAR DI BEI - Dini Novianti; Soemaryono Soemaryono (Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze and empirically examine the influence of green accounting, material flow cost accounting, and environmental performance on sustainable development in food and beverage sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The variables were measured through indicators of environmental cost disclosure, the application of cost approaches in the production process, environmental performance disclosure through PROPER, and the achievement of long-term sustainable development. A quantitative approach with purposive sampling was employed, resulting in 62 eligible data points from a total population of 83 companies. The findings indicate that these three factors collectively have a significant influence on sustainable development in the food and beverage sector, highlighting the importance of integrating environmental considerations into business strategies to achieve long-term sustainability